Local-scale impacts of water hyacinth on water quality in a hypereutrophic lake - Corman, Jessica R.; Roegner, Amber; Ogari, Zachary; Miller, Todd R.; Aura, Christopher M. (Frontiers in Water, 2023)
Increased nutrient concentrations have been linked to water quality impairments across the world. In Lake Victoria, the second largest freshwater lake in the world, decades of eutrophication have challenged water quality management and led to conditions with compromising levels of cyanobacteria and cyanotoxins. Our study focuses on Winam Gulf, where a resurgence of water hyacinth has led to renewed challenges with navigation and anoxia, but also may present a local-scale opportunity for water quality improvements. Over the course of 1.5 years, we conducted three, in situ experiments to vary levels of water hyacinth density and determined its effects on lake water nutrient composition, biochemical parameters (chlorophyll a, cyanotoxins), and fecal indicators (fecal coliforms and Escheria coli). We found the impacts of water hyacinth strongest when the plant was already present in the Gulf – ie, small-scale removal of the plants led to decreases in coliforms (F1,11=11.14, p<0.01), E. coli (F1,11=22.95, p<0.001), and total microcystins (F1,9=3.47, p=0.095). The majority of samples collected had both E coli and microcystin concentrations, notably exceeding World Health Organization guidelines for drinking water. Our data suggest that magnitude of scale, as well as season considerations such as rainfall and background level of water hyacinth, will strongly influence the phytoremediation potential of water hyacinth. The data encourages rigorous public health communication to reduce occupational and household risks, as well as further exploration of remediation potential of native and introduced macrophytes.